Waste management at kartasuro traditional market, Sukoharjo Regency - Nurbaya Fiqi; Budihardjo Mochamad Arief; Warsito Budi (E3S Web of Conferences)
Kartasura traditional market is a people’s market located in Kartasura District, Sukoharjo Regency. This market produces organic and inorganic waste. The purpose of the study was to analyze waste management at Kartasura Traditional Market. The type of research was descriptive qualitative. The informants of the study were cleaners, traders, market heads, staff of the Sukoharjo Regency Cooperative UKMK Trade Service, and the head of the Sukoharjo Regency Environmental Service UPTD. The object of the study was the waste management system at Kartasura Traditional Market based on the Decree of the Minister of Health Number 519 / MENKES / SK / VI / 2008 concerning guidelines for organizing a healthy market environment, PMK Number 17 of 2020 concerning Healthy Markets and SNI 519-2454-2002 concerning Technical Operational Procedures for Urban Waste Management. Data analysis used the Miles and Huberman model, namely Data Reduction, Data Presentation, and Conclusions or Verification. Research results management garbage in traditional markets Not yet in accordance with condition health, technology management rubbish sustainable that can applied is biomass and waste banks. Need done effort management trash that can contribute to sustainability environment is recycle repeat 3R.